History of the Kingdom of Siam and of the revolutions that have caused the overthrow of the empire, up to A.D. 1770 - Cartwright, Basil Osborn (Printed at the American Presbyterian Mission Press, 1908)
The first kings of Siam -- The reign of Chao Narai -- Tha revolt of the Macassars -- The revolution that brought about the downfall of Faulcon and the French -- The breach between the French and the Usurper -- The persecution of the christians after the departure of Des Farges -- Events leading up to the revolution of 1760 -- The revolution of 1760 -- The revolution of 1767 -- The misfortunes of the Europeans after the revolution -- After the revolution 1767 -- Advantages that might accrue from commercial neighbouring relations with Siam and the Kingdoms -- Tonkin